Faktor-Faktor yang Mempengaruhi Keputusan Konsumen dalam Membeli Produk di Hungry Bird Coffee Canggu - Nishyah Mardhiyyah; Agung Sri Sulistyawati; Irma Rahyuda (Jurnal Kepariwisataan dan Hospitalitas, 2019)
This study aims to analyze the factors that influence consumer decisions of buying products in Hungry Bird Coffee Canggu and to find out the dominant factors that influence consumer decisions of buying products in Hungry Bird Coffee Canggu. This research was conducted at Hungry Bird Coffee Canggu with respondents totaling 100 respondents, the sample in this study was selected using the accidental sampling method. The data in the study were analyzed using exploratory factor analysis which was supported by the SPSS version 17.0 for windows statistical program. The results of this research are: 1) The factors that influence consumer decisions of buying products in Hungry Bird Coffee Canggu produce 8 factors formed, namely the first factor is given the name of culture that has an eigenvalue of 6.211, place factor has an eigenvalue of 2.689, promotion factor has eigenvalue value of 2.394, process factor has an eigenvalue of 1.847, social factors have eigenvalue of 1.555, product factor has an eigenvalue of 1.314, price factor has an eigenvalue of 1.221, physical evidence factor has an eigenvalue of 1.025. 2) Cultural factors are the most dominant influencing consumer decisions of buying products in Canggu's Hungry Bird Coffee. This factor consists of three forming indicators, namely citizenship, geographical area, and lifestyle. The advice that can be given for this research is that Hungry Bird Coffee improves their marketing methods through advertisements, websites or social media, gives promos, seeks solutions to maintain old consumers and also attracts new consumers, and provides unique concepts for interior design and café exterior.